E-Modul dalam Mata Pelajaran Informatika untuk Upaya Meningkatkan Kemampuan Computational Thinking dan Literasi Digital - Maulidiyah, Hanun; ., Mustaji; Susarno, Lamijan Hadi (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This article aims to investigate e-modules in informatics subjects to improve computational thinking and digital literacy. Data were collected through classroom observation, interviews with teachers and students, and analysis of creative products produced by students during the learning process. This research uses the literature study method, which is a method of collecting data by conducting a study and interpretation of various literature sources in the form of books, journals, notes, or reports related to the theme of the research conducted Articles using primary data sources are sourced from online applications such as google, google scholar, science Direct and books as sources of information and in review articles. E-modules are valuable media in improving learning, helping learners develop Computational Thinking skills, and improving their digital literacy in the modern technological era. In addition, this article also reveals that developing e-modules for informatics subjects improves computational thinking skills and overall digital literacy, this research concludes that in today's digital era, technology has had a significant influence on various aspects of life, including education. In the context of education, it is important to keep up with the rapid development of information and communication technology in the 21st century. Technology-based learning media, such as e-modules, have proven to be an efficient tool in the learning process. In this context, e-modules emerge as a solution that can help improve learners' understanding of informatics materials, develop their computational thinking skills, and improve their digital literacy. In this study, e-modules are described as a learning media that can help learners learn independently, improve their understanding of informatics materials, and improve computational skills. In addition, e-modules assist learners in developing their digital literacy, including the ability to access, evaluate, and use information in digital form.